2006
DOI: 10.1111/j.1365-2141.2006.06334.x
|View full text |Cite
|
Sign up to set email alerts
|

Human leucocyte antigen‐C in B chronic lymphocytic leukaemia

Abstract: Summary This study aimed at characterising the distribution of human leucocyte antigen (HLA)‐C alleles in a large group of patients with B chronic lymphocytic leukaemia from Southeastern Spain. Ninety‐eight adult patients and 194 geographically and ethnically matched controls were studied. HLA‐C was determined by polymerase chain reaction sequence‐specific primers (PCR‐SSP) and PCR‐sequence‐specific oligonucleotides (SSO) methods. The HLA‐Cw*16 allele frequency was found to be significantly increased amongst p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Study results of HLA class I alleles and CLL risk have been mixed. A small study of 98 patients in Spain reported the HLA‐Cw*16 allele to be associated with a 2.69 increased risk of developing CLL . Among CLL patients with a family history of CLL, the HLA‐DRB1*11 alleles were associated with increased CLL risk ( P ‐value = 0.009) .…”
Section: Chronic Lymphocytic Leukaemia/small Lymphocytic Lymphomamentioning
confidence: 99%
“…Study results of HLA class I alleles and CLL risk have been mixed. A small study of 98 patients in Spain reported the HLA‐Cw*16 allele to be associated with a 2.69 increased risk of developing CLL . Among CLL patients with a family history of CLL, the HLA‐DRB1*11 alleles were associated with increased CLL risk ( P ‐value = 0.009) .…”
Section: Chronic Lymphocytic Leukaemia/small Lymphocytic Lymphomamentioning
confidence: 99%
“…Apart of a few studies [4,16,[19][20][21][22][23][24][25][26] in which the frequency of HLA alleles has been determined in CLL patients from some ethnic populations, association of HLA alleles and CLL prognosis has not been well studied, especially in the Asian CLL patients. In a prior study we reported the frequency of some HLA class I A, B and C antigens in a limited number of CLL patients using the serological microlymphocytotoxicity technique [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a relationship between HLA polymorphisms and susceptibility to certain hematologic malignancies such as chronic lymphocytic leukemia, multiple myeloma, and acute lymphoblastic leukemia. [9][10][11] However, there is little information about the relationship between HLA polymorphisms and susceptibility to developing B-NHL or their outcomes. [12][13][14][15][16] Focusing on diffuse large B-cell lymphoma (DLBCL), some associations between HLA specificities and this B-NHL subtype have been described, as well as with other genetic polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we describe for the first time the role of HLA polymorphisms in the prognosis of DLBCL patients receiving rituximabbased regimens as first-line treatment. Our results show that the presence of the HLA-DRB1*01 and the absence of HLA-C*03 polymorphism are associated with susceptibility to DLBCL, while the HLA-B44 supertype, especially the presence of HLA-B*18 and HLA-B*44 polymorphisms, have an independent influence on survival.The HLA system has been related to susceptibility to several hematologic and nonhematologic diseases, [9][10][11]36 including a variety of HLA polymorphisms associated with B-NHL development and outcome. [12][13][14][15][16] However, this feature has not been extensively studied specifically in DLBCL, although some data suggest an association between HLA subtypes and disease susceptibility (ie, a higher incidence of HLA-DRB1*04:01 allele in this lymphoma subgroup).…”
mentioning
confidence: 99%